PENGARUH KREDIBILITAS MANAJER DAN POLA KOMUNIKASI TERHADAP KINERJA KARYAWAN (STUDI PADA HOTEL ATRIA MALANG) - M Reza Ishadi Fadillah; Citra Rani Angga Riswari (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
Atria Malang Hotel as a hospitality service industry faces demands to improve employee performance through effective organizational communication management. This study aims to analyze the influence of Manajer credibility and organizational communication patterns on employee performance. This research uses a quantitative approach with a survey method. The independent variables are Manajer credibility, which includes competence, appearance, and attitude, and organizational communication patterns, which consist of formal and informal communication. The dependent variable is employee performance. The theoretical framework applied includes behaviorism theory, stimulus-organism-response theory, communicator credibility concepts, organizational communication, and employee performance. The population of this study consists of employees of Atria Malang Hotel who are involved in daily organizational communication processes. Data were collected through questionnaires and analyzed using statistical techniques to examine both simultaneous and partial effects among variables. The results show that Manajer credibility and communication patterns have a significant effect on employee performance, both jointly and partially. High Manajer credibility enhances trust, message acceptance, and work discipline, while effective communication patterns facilitate information flow, coordination, and working relationships. These findings indicate that the success of service organizations is determined not only by operational capabilities but also by the quality of leadership communication in building a positive and conducive work climate.   Keywords: Manajer Credibility, Communication Patterns, Organizational Communication, Employee Performance, Hotel.